Transcutaneous electrical nerve stimulation and conditioned pain modulation influence the perception of pain in humans. (6th May 2013) - Liebano, R.E.; Vance, C.G.; Rakel, B.A.; Lee, J.E.; Cooper, N.A.; Marchand, S.; Walsh, D.M.; Sluka, K.A.
Abstract Background Research in animal models suggests that transcutaneous electrical nerve stimulation (TENS) and conditioned pain modulation (CPM) produce analgesia via two different supraspinal pathways. No known studies have examined whether TENS and CPM applied simultaneously in human subjects will enhance the analgesic effect of either treatment alone. The purpose of the current study was to investigate whether the simultaneous application of TENS and CPM will enhance the analgesic effect of that produced by either treatment alone. Methods Sixty healthy adults were randomly allocated into two groups: (1) CPM plus active TENS; (2) CPM plus placebo TENS. Pain threshold for heat (HPT) and pressure (PPT) were recorded from subject's left forearm at baseline, during CPM, during active or placebo TENS, and during CPM plus active or placebo TENS. CPM was induced by placing the subjects' contralateral arm in a hot water bath (46.5 °C) for 2 min. TENS (100 μs, 100 Hz) was applied to the forearm for 20 min at a strong but comfortable intensity. Results Active TENS alone increased PPT (but not HPT) more than placebo TENS alone (p = 0.011). Combining CPM and active TENS did not significantly increase PPT (p = 0.232) or HPT (p = 0.423) beyond CPM plus placebo TENS. There was a significant positive association between PPT during CPM and during active TENS (r2 = 0.46; p = 0.003). Conclusions TENS application increases PPT; however, combining CPM and TENS does not increase the CPM's hypoalgesic response. CPM effect on PPT is associated with the effects of TENS on PPT.